Peningkatan Partisipasi Guru Pada Pendidikan Dasar Melalui Sertifikasi Guru - Loso Judijanto; Heru Kreshna Reza; Melly Susanti (Journal on Education, 2024)
In the field of education, teachers face latent problems related to economic welfare, so the government is trying to provide a teacher certification program. In an effort to increase teacher engagement in teaching students at the Islamic primary education level, this research will examine teacher certification. This type of research combines literature study methodology with a qualitative approach. Scientific literature which includes books, papers, seminars, and final assignments (thesis, thesis, dissertation) serves as a source of information and material for research analysis. This information comes from reliable sources such as Sinta and Google Scholar. The findings of this study indicate that the implementation of teacher certification is expected to improve teachers' competencies so as to improve educational standards. The four components of competence are; Pedagogical, character, professional, and social mentioned in the government regulation on national education standards (article 28) and the law on teachers and lecturers (article 10).